The USSR Victory in World War II and the Emergence of the Independent Republic of Indonesia - L. M. Efimova (Vestnik MGIMO-Universiteta)
Victorious ending of the World War 2 on May, 9, 1945, stroke a crushing blow on the military axis Berlin - Rome - Tokyo. The USSR played a decisive role both on European and Asian fronts. Fulfilling its allied duty the Soviet Union entered the war in the Far East on 9 August, 1945 and defeated the Japanese army in Manchuria. This act became a great contribution to liberation of Asian peoples from the Japanese occupation. On the 17 August 1945 the Republic of Indonesia declared its independence. The recognition on the side of international community as well as diplomatic support became\e vital for the survival of the newly emerged Republic.The Soviet victory together with the allied nations in the Second World War, the new status of the USSR as a superpower, its constant anticolonial stance stimulated former colonies to appeal to the Soviet Union for backing and support. One of the first was the Republic of Indonesia, to which the USSR rendered all kind of help and encourages. The present article which is a result of the study of newly available documents from several recently opened Soviet archives shows the Soviet backing of Indonesia in the UN, its diplomatic recognition, in strengthening of Indonesian status as a sovereign state on the international arena as a whole.